Psychometric Properties and Characteristics of the North‐East Visual Hallucinations Interview in Parkinson's Disease. Issue 5 (16th March 2017) - Holiday, Kelsey A.; Pirogovsky‐Turk, Eva; Malcarne, Vanessa L.; Filoteo, J. Vincent; Litvan, Irene; Lessig, Stephanie L.; Song, David; Schiehser, Dawn M.
Abstract: Background: Visual hallucinations (VH) are a common symptom experienced by individuals with Parkinson's disease (PD); however, a validated measure of VH has yet to be established for this population. The North‐East Visual Hallucinations Interview (NEVHI), a promising VH measure, has not been well validated in patients with PD. The aim of this study was to evaluate the convergent and discriminant validity of the NEVHI as well as the proportional identification and characteristics of VH in PD. Methods: One hundred seventeen individuals with PD completed the NEVHI along with evaluations of psychological, cognitive, motor, and visual functioning as measures of convergent and divergent validity. The hallucination items from the Neuropsychiatric Inventory (NPI) and the Movement Disorder Society‐sponsored revision of the Unified Parkinson's Disease Scale (MDS‐UPDRS) were used to assess convergent validity. Results: The NEVHI identified 20.5% of patients who had PD with VH, which included all individuals identified by the MDS‐UPDRS and NPI and 9 additional individuals who were not identified using the other measures. The NEVHI was strongly correlated with the MDS‐UPDRS hallucinations item and weakly correlated with the NPI VH item. Weak to nonsignificant correlations were observed between the NEVHI and measures of psychological, cognitive, motor, visual, and demographic characteristics. Conclusion: The NEVHI identified a greater number of individuals with VH than either the MDS‐UPDRS or the NPI. The current results demonstrated good convergent validity between the NEVHI and a clinician‐administered, patient‐report measure of VH and excellent divergent validity, supporting the NEVHI as a valid and preferable measure for assessing the presence of VH in PD